ANALISIS KUALITAS KONTEN DAN AKURASI TERHADAP KEPUASAN GURU MENGGUNAKAN APLIKASI E-RAPOR DI SMK NEGERI 3 PARIAMAN - Ayu Eka Putri; Ganefri (Universitas Yudharta Pasuruan, 2020)
This study aims to reveal content and test the satisfaction of teachers using e-report cards at SMK Negeri 3 Pariaman. This research uses quantitative research methods using correlational. The study population was all teachers who taught at SMK Negeri 3 Pariaman who took 74 people with a sample of 12 people taken by proportional random sampling. Data collection techniques using a research questionnaire. The questionnaire was tested on 12 members who were not included in the sample, then conducted a validity and reliability test. Testing the data analysis requirements and hypotheses with the normality test, linearity test, multicollinearity test and regression analysis. The analysis results obtained Content Variable (X1) has a proportion of Teacher Satisfaction (Y), with a significance value of 0,000 <0.05, Fcount> Ftable (8,478> 1,812), Accuracy Variable (X2) has a relationship with Teacher Satisfaction (Y), with a significance value of 0,000 <0.05, Fcount> Ftable (11,397> 1,812). Content Variable (X1 Accuracy (X2) has a composition together with User Satisfaction (Y) E-Rapor in SMK Negeri 3 Pariaman, with a significance value of 0,000 <0.05 and Fcount> Ftable (65,177> 4.04).